Development of Hypoallergenic “Pindang” Tongkol (Euthynnus affinis) Processed by Pressurized Heating - Regina Caely Saing; Nur Wulandari; Nurheni Sri Palupi (The University of Lampung, 2026)
Tongkol (Euthynnus affinis) or Mackerel tuna consumption in Indonesia remains limited due to the presence of the allergenic protein parvalbumin. This study aimed to evaluate the chemical composition, physical properties, protein molecular weight profile, and allergenicity of pindang tongkol processed by pressurized heating. A Completely Randomized Design with three autoclave time treatments (15, 20, and 25 min) at 150 °C and 0.103 MPa was applied. Chemical composition and physical properties were analyzed, protein profiles were determined using SDS-PAGE, protein concentration by the Bradford method, and texture by Texture Profile Analysis (TPA). Allergenicity was assessed qualitatively by immunoblotting and quantitatively by ELISA. Pressurized heating altered the chemical composition and physical properties of tongkol. SDS-PAGE revealed protein band at 10–12 kDa, suspected to be parvalbumin, in all samples; however, immunoblotting detected parvalbumin only in the raw sample. Allergen content decreased by 71, 86, and 97% after 15, 20, and 25 min of heating, respectively, compared to raw fish. Pressurized heating during pindang processing effectively reduced allergenicity and may improve the safety of mackerel tongkol consumption for individuals with fish protein hypersensitivity